Feasibility and Acceptability of a Mobile Intervention to Improve Treatment Adherence in Bipolar Disorder: A Pilot Study. (July 2014) - Wenze, Susan J.; Armey, Michael F.; Miller, Ivan W.
We evaluated the feasibility and acceptability of a 2-week-long ecological momentary intervention (EMI), delivered via personal digital assistants (PDAs), to improve treatment adherence in bipolar disorder. EMIs use mobile technology to deliver treatment as clients engage in their typical daily routines, in their usual settings. Overall, participants ( N = 14) stated that EMI sessions were helpful, user-friendly, and engaging, and reported satisfaction with the timing and burden of sessions, as well as the method of delivery. All participants completed the study, and all PDAs were returned undamaged. On average, participants completed 92% of EMI sessions. Although this study was not designed to assess efficacy, depression scores decreased significantly over the study period and data suggest relatively high rates of treatment adherence; missed medication was reported 3% of the time and three participants reported missing a total of six mental health appointments. Negative feedback largely involved technical and logistical issues, many of which are easily addressable. These preliminary findings add to the growing body of literature indicating that mobile-technology-assisted interventions are feasible to implement and acceptable to patients with serious mental illnesses.